2020
DOI: 10.1186/s40621-020-00254-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mobile safety center's impact on pediatric home safety knowledge and device use

Abstract: Background: A Mobile Safety Center (MSC) is designed to remove financial accessibility barriers to home safety by providing education and safety devices within local communities. The objective of this study was to evaluate the impact of an MSC on pediatric home safety knowledge and device use. Methods: We conducted a prospective home safety interventional study. Parents and grandparents with children at home were recruited at community events attended by the MSC. Participants completed a pre-test survey assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Of our 50 surveyed participants, 29 (58%) completed follow-up 1, 30 (60%) completed follow-up 2, and 26 (52%) completed both. Some participant demographics, including gender, age, race/ethnicity, level of education, marital status, employment, and income level were previously reported in our prior study; notably, while female-predominant (90%), participant racial/ethnic breakdown resembled the population of the Pittsburgh area, while median annual income ($25,000 - $34,999) was lower than the local average [ 8 ]. The majority of participants were employed (56%), married or in a domestic partnership (60%), and 80% finished high school or held an equivalent degree [ 8 ].…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Of our 50 surveyed participants, 29 (58%) completed follow-up 1, 30 (60%) completed follow-up 2, and 26 (52%) completed both. Some participant demographics, including gender, age, race/ethnicity, level of education, marital status, employment, and income level were previously reported in our prior study; notably, while female-predominant (90%), participant racial/ethnic breakdown resembled the population of the Pittsburgh area, while median annual income ($25,000 - $34,999) was lower than the local average [ 8 ]. The majority of participants were employed (56%), married or in a domestic partnership (60%), and 80% finished high school or held an equivalent degree [ 8 ].…”
Section: Resultsmentioning
confidence: 79%
“…Some participant demographics, including gender, age, race/ethnicity, level of education, marital status, employment, and income level were previously reported in our prior study; notably, while female-predominant (90%), participant racial/ethnic breakdown resembled the population of the Pittsburgh area, while median annual income ($25,000 - $34,999) was lower than the local average [ 8 ]. The majority of participants were employed (56%), married or in a domestic partnership (60%), and 80% finished high school or held an equivalent degree [ 8 ]. Of the above-noted demographics, binary logistic regression revealed that only marital status was an independent predictor of follow-up completion (χ 2 (4) = 11.443, p = 0.022), with participants who were married or in a domestic partnership 5.23 times more likely to complete both follow-ups compared to single participants.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations